Islamic Educational Values in Integrated Basic Cultural Sciences at the Central Java Coastal Campus - Sholeh, Muh. Muhtar Arifin; Zaenurrosyid, A.; Nurhamidah, Idha; Nuridin; Hassan, Mahmudul (Al-Hayat: Journal of Islamic Education, 2026)
This study aims to examine two fundamental aspects: first, the necessity of integrating Islamic values into the Basic Cultural Sciences (Ilmu Budaya Dasar/IBD) course, and second, the identification of relevant Islamic values to be incorporated into the curriculum. Religious values are regarded as crucial elements in shaping students’ character, playing a strategic role in developing intellectual capacity, ethical behaviour, and positive attitudes. The research employed a mixed-methods approach, combining field research and literature review (quantitative and qualitative approaches). The research locus was the Faculty of Islamic Studies (Fakultas Aama Islam/FAI). The sample consisted of 39 students in their fifth semester or higher who had completed the IBD course, drawn from a population of approximately 45 students in one class. Qualitative data were obtained through in-depth interviews with students, lecturers, and foundation administrators, both within the campus environment and in student pesantren (boarding schools). Data collection instruments included questionnaires and semi-structured interview guides. The findings reveal a set of essential Islamic values to be integrated into IBD lectures, namely truth, honesty, love and respect, justice, peace, unity, tolerance, patience, sincerity, accountability, consistency, and gratitude. Truth and honesty were the most dominant values identified. Through communal living in campus boarding facilities, these values were reinforced. The novelty of this study lies in its proposed model integrating noble Islamic values into curricula, enhancing moral and academic development, and fostering a Qur’anic generation embodying these values in all life domains. This study has several limitations. The sample size was relatively small and limited to one faculty, which may restrict the generalizability of the findings to broader educational contexts. In addition, the qualitative insights were based on a specific institutional setting, students who live in campus-based pesantren. So the lived experiences supporting value internalisation may differ in non-boarding environments. Despite these constraints, the originality of this research lies in its systematic formulation of an integrative model that embeds core Islamic values within the IBD curriculum. This model not only strengthens students' moral and intellectual development but also offers a replicable framework for Islamic higher education institutions seeking to cultivate a Qur'anic generation grounded in character, ethics, and holistic academic excellence.